2007
DOI: 10.1111/j.1472-765x.2007.02114.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lactococcus garvieae isolated from radish and broccoli sprouts that exhibited a KG+phenotype, lack of virulence and absence of a capsule

Abstract: Aims:  To identify Lactococcus garvieae isolates from radish and broccoli sprouts and compare them with virulent and less virulent mutant strains obtained from yellowtails with regard to KG phenotype, presence of a capsule and virulence towards yellowtails and mice. Methods and Results:  Comparative 16S rRNA gene sequence analysis of six isolates obtained from radish and broccoli sprouts indicated that they were L. garvieae (similarity >99%). They were compared with KG9502, Lg2 and ATCC49156 strains obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 17 publications
(24 reference statements)
3
42
0
Order By: Relevance
“…In fact, L. garvieae is currently considered a potential emerging zoonotic pathogen (10). In addition, this microorganism is widespread in the environment, having been isolated from wild birds, rivers, sewage waters, and a wide variety of foodstuffs, including vegetables, meat, sausages, and, particularly, artisan dairy products (11)(12)(13).…”
mentioning
confidence: 99%
“…In fact, L. garvieae is currently considered a potential emerging zoonotic pathogen (10). In addition, this microorganism is widespread in the environment, having been isolated from wild birds, rivers, sewage waters, and a wide variety of foodstuffs, including vegetables, meat, sausages, and, particularly, artisan dairy products (11)(12)(13).…”
mentioning
confidence: 99%
“…It is isolated from buffalos with mastitis (Teixeira et al, 1996) and clinical specimens of human blood, urine, and skin (Vinh et al, 2006;Wang, 2007;Villani et al, 2001). Moreover, L. garvieae is isolated from various kinds of food products including cow's milk (Villani et al, 2001), cheeses (Alegr´ıa et al, 2009;Fortina et al, 2007;El-Baradei et al, 2007;Florez & Mayo, 2006), meat products (Aquilanti et al, 2007;Barakat et al, 2000;Rantsiou et al, 2005) and sprout (Kawanishi et al, 2007). L. garvieae is detected in most of Egyptian cheeses (El-Baradei et al, 2005) and also found in Jordanian cheese (Alrabadi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the yellowtail-derived L. garvieae isolates appeared to be homogenous and very different from isolates obtained from other fish, terrestrial animals, and food plants (4,5,6). Recently, of 146 L. garvieae strains isolated from 1999 to 2006 from yellowtail farms in three prefectures in Japan, 46 strains had high levels of resistance to EM, LCM, and tetracycline and were found to be carrying transferable R plasmids that carry ermB and tetS genes, as evidenced by conjugation, Southern blotting, and PCR methods (7).…”
mentioning
confidence: 99%